2022
DOI: 10.1186/s12871-022-01694-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intratracheal dexmedetomidine combined with ropivacaine on postoperative sore throat: a prospective randomised double-blinded controlled trial

Abstract: Background The present study aimed to investigate whether intratracheal dexmedetomidine combined with ropivacaine reduces the severity and incidence of postoperative sore throat after tracheal intubation under general anaesthesia. Methods Two hundred patients with American Society of Anaesthesiologists physical status I-II who were subjected to general anaesthesia were randomly divided into four groups, namely, Group D, Group R, Group DR and Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…32 In addition, we found that the highest incidence of delirium occurred on the first day after surgery (Figure 2), which was consistent with the view that the rate of delirium is highest during the early postoperative period. 33 In line with a previous report, 16 this study confirmed that intratracheal dexmedetomidine reduced the incidence of sore throat at 2 hours after surgery. This was probably because dexmedetomidine prolonged the duration of ropivacaine and improved the efficacy of postoperative local analgesia.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…32 In addition, we found that the highest incidence of delirium occurred on the first day after surgery (Figure 2), which was consistent with the view that the rate of delirium is highest during the early postoperative period. 33 In line with a previous report, 16 this study confirmed that intratracheal dexmedetomidine reduced the incidence of sore throat at 2 hours after surgery. This was probably because dexmedetomidine prolonged the duration of ropivacaine and improved the efficacy of postoperative local analgesia.…”
Section: Discussionsupporting
confidence: 89%
“…Keshri et al 27 reported that a loading dose of 0.5 µg/kg intravenous dexmedetomidine has the minimum side effects in reducing the hemodynamic stress response in geriatric patients undergoing spine surgery when compared with 1 µg/kg dexmedetomidine. The dose of intratracheal dexmedetomidine was 1 µg/kg for patients aged 20 to 65 in our previous study, 16 and the intratracheal route of dexmedetomidine is rapidly absorbed through the bronchial and alveolar capillary network. 28 Considering its safety and effectiveness in elderly patients aged 60 years or above in this study, the final dose for the IV route and intratracheal route of dexmedetomidine is equal to 0.6 µg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis concluded that though drugs such as lidocaine—intravenous (IV), intracuff, topical, or intratracheal (IT), dexmedetomidine IV, and opioids IV such as remifentanil and fentanyl showed better odds of reducing moderate to severe cough at extubation and among these options, IV dexmedetomidine has emerged as the most favourable drug in terms of highest cumulative rank for decreasing the frequency of moderate to severe emergence. [ 2 ] More recently, the use of IT route of dose 0.5 mcg/kg for the administration of dexmedetomidine has been introduced[ 3 4 ] but there is a paucity of studies which have used IT dexmedetomidine. Further, there are no dose comparing studies comparing different doses of IT dexmedetomidine for alleviating cough at extubation.…”
Section: Introductionmentioning
confidence: 99%